2002
DOI: 10.1785/0120010101
|View full text |Cite
|
Sign up to set email alerts
|

Source Parameters of Earthquakes in Eastern and Western North America Based on Finite-Fault Modeling

Abstract: The ground motion from large earthquakes is often predicted based on finite-fault modeling, in which the fault plane is discretized into small independently rupturing subfaults; the radiation from all subfaults is summed at the observation point. Despite the success of the method in matching observed ground-motion characteristics, the physical interpretation of the subfaults has remained largely unclear, and a rationale for the choice of the subfault attributes has been lacking. Two key parameters-the subfault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(71 citation statements)
references
References 50 publications
(32 reference statements)
6
65
0
Order By: Relevance
“…The lower corner frequency f C1 is related to fault dimensions or rupture duration, whereas the physical meaning of the second corner frequency f C2 is not so clear. Papageorgiou and Aki (1983) and later Beresnev and Atkinson (2002) relate f C2 to the characteristic size of an assumed crack-like subsource, whereas Gusev (2013) believes that it is related to the local rise time, T R , and to the slip-pulse width l. In the following, the main notion is the rms average acceleration source spectrum…”
Section: G11d: the New Scaling Lawmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower corner frequency f C1 is related to fault dimensions or rupture duration, whereas the physical meaning of the second corner frequency f C2 is not so clear. Papageorgiou and Aki (1983) and later Beresnev and Atkinson (2002) relate f C2 to the characteristic size of an assumed crack-like subsource, whereas Gusev (2013) believes that it is related to the local rise time, T R , and to the slip-pulse width l. In the following, the main notion is the rms average acceleration source spectrum…”
Section: G11d: the New Scaling Lawmentioning
confidence: 99%
“…For Japan, the absolute level is log 10 A HF (M w = 7) = 26.22 after Irikura and Miyake (2011). However, many authors (Toro et al, 1997;Beresnev and Atkinson, 2002;Halldorsson and Papageorgiou, 2005) identified scaling behaviour of AHF that violates similarity. All of them found slower increase of A HF vs. M 0 as compared to (4).…”
Section: G83 Key Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For Japan, the absolute level is log 10 A HF (M w = 7) = 26.22 after Irikura and Miyake (2011). However, many authors (Toro et al, 1997;Beresnev and Atkinson, 2002;Halldorsson and Papageorgiou, 2005) identified scaling behaviour of AHF that violates similarity. All of them found slower increase of A HF vs. M 0 as compared to (4).…”
Section: G83 Key Featuresmentioning
confidence: 99%
“…Okubo and Aki 1987;Lee and Schwarcz 1995). The self-similarity of earthquake slip distributions is an essential physical characteristic of earthquake kinematics and was discussed in previous studies (Beresnev and Atkinson 2002;Manighetti et al 2005Manighetti et al , 2007Wesnousky 2008;Klinger 2010). Wesnousky (2008) analyzed earthquake rupture traces and coseismic surface slip and obtained the scaling relationship between the slip and rupture length for strike-slip earthquakes.…”
Section: Introductionmentioning
confidence: 99%